Non-invasive biomagnetic assessment of gastrointestinal motility in a loperamide-induced constipation model - Stoppa, Erick Guilherme [UNESP]; Soares, Guilherme Augusto [UNESP]; Buranello, Lais Pereira [UNESP]; Portela, Luiz Marcos Frediani [UNESP]; Justulin, Luiz Antônio [UNESP]; Américo, Madileine Francely; Di Stasi, Luiz Claudio [UNESP]; Miranda, José Ricardo de Arruda [UNESP] (FapUNIFESP (SciELO), 2024)
Constipation is a disorder of the gastrointestinal (GI) and some of the main etiological mechanisms are directly related to changes in GI physiology. The capacity to carry out paired assessments and measure GI parameters under the influence of constipation is a relevant point in selecting a suitable methodology. We aimed to perform a non-invasive investigation of gastrointestinal motility in constipated rats using the alternating current biosusceptometry system (ACB). The animals were split into two groups: the pre-induction stage (CONTROL) and post-induction loperamide stage (LOP). We assessed GI motility parameters using the ACB system. Colon morphometric and immunohistochemical analyses were performed for biomarkers (C-kit) for interstitial cells of Cajal (ICC). Our results showed a significant increase in gastrointestinal transit in the LOP group in addition to a reduction in the dominant frequency of gastric contraction and an arrhythmic profile. A change in colonic contractility profiles was observed, indicating colonic dysmotility in the LOP group. We found a reduction in the number of biomarkers for intestinal cells of Cajal (ICC) in the LOP group. The ACB system can evaluate transit irregularities and their degrees of severity, while also supporting research into novel, safer, and more efficient treatments for constipation.
Keywords: Alternating Current Biosusceptometry (ACB); Colonic Motility; Constipation; Gastrointestinal Transit; Loperamide